Unlocking the dual healing powers of plant-based metallic nanoparticles: managing diabetes and tackling male infertility challenges - Siddiqa, Ayesha; Qureshi, Rahmatullah; Yasmin, Ghazala; Rafique, Shaista; Zafar, Noor-Ul-Ain; Hussain, Chudary Sadam; Rehman, Sana ur; Naheed, Neelum (Frontiers in Endocrinology, 2025)
Diabetes mellitus (DM) is a severe metabolic disorder characterized by an increase in blood glucose level due to insufficient insulin production or failure of insulin action on targeted tissues or both. DM impacts male reproductive health across four aspects: ejaculation, erectile dysfunction, structural alterations in reproductive organs, and alterations in semen quality. The population of male individuals with diabetes is steadily rising, paralleled by an increase in fertility issues among men. A WHO report states that diabetes mellitus affects about 171 million (2.8%) persons worldwide. Anti-diabetic medications that are now on the market are expensive and have several negative effects, including cardiac, hepatic, and renal failure in diabetic patients. Keeping in view, this review emphasizes the limitations of currently used synthetic anti-diabetic drugs and provides the progress in the development of phytogenic metallic NPs (NP)in the treatment of diabetes and associated male infertility. To collect data, various databases were examined, including Springer Link, Google Scholar, PubMed, Wiley Online Library, and Science Direct. Several studies and research reports based on nanotechnological approaches in the formulation of anti-diabetic drugs have pointed out the fact that research in the formulation of nanodrugs has improved strategies for combating diabetes and associated male infertility based on the plausible molecular mechanism of action of the drugs. These nanodrugs have been observed to significantly influence regulatory mechanisms through their effects on pancreatic α-amylase, intestinal α-glucosidase, insulin action, and glucose uptake across various in vivo and in vitro systems. Moreover, integrating nanotechnological methodologies with the exploration of herbal compounds further enhances the understanding of their chemical potential. This synergistic approach may pave the way for identifying novel drug candidates with exceptional therapeutic efficacy, offering significant advantages in the management of diabetes and associated male infertility for the betterment of humanity. Furthermore, the personalized design of plant-based metallic NPs has the potential to significantly advance precision medicine techniques for the treatment of male infertility and diabetes.